A flame retardant anti-dripping fiber with different shrinkage and its preparation method
Patent Information
- Application Number
- CN202311844723.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-28
AI Technical Summary
涤纶由于结构特征,在使用过程中存在手感较硬、上色率低、透气性差、吸湿量小等缺点
[0009] The beneficial effects of this invention are as follows: This invention uses a copolymerization method, adding a compound flame retardant during the polycondensation reaction to form a copolymer-modified polyester melt. This melt is then spun using a melt-spinning process to obtain a heterogeneous shrinkage flame-retardant and anti-dripping fiber. This fiber possesses heterogeneous cross-section and heterogeneous shrinkage characteristics, exhibiting excellent wool-like properties. The compound flame retardant contains methacrylate-based silicone resin micropowder, whitened red phosphorus, and tetraquid zinc oxide whiskers. The combination of methacrylate-based silicone resin micropowder and whitened red phosphorus provides excellent flame retardant effects. The tetraquid zinc oxide whiskers, utilizing their spatial structure, can be embedded within the fiber, effectively preventing the fabric from melting and dripping when heated, thus achieving flame retardant and anti-dripping functions.
Smart Images

Figure CN117802617B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile and chemical fiber production technology, specifically to a differential shrinkage flame-retardant and anti-dripping fiber and its preparation method. Background Technology
[0002] Polyester has become the most widely used and consumed synthetic fiber. Due to its structural characteristics, polyester suffers from drawbacks such as a stiff hand feel, low dyeing yield, poor breathability, and low moisture absorption. In recent years, numerous methods have emerged to address these shortcomings, including: profile spinning technology, which makes the fiber cross-section resemble that of natural fibers; fiber micronization technology, which increases moisture absorption and improves hand feel; composite spinning technology, which uses other polymers for composite spinning; fiber surface modification, which uses chemical methods to add hydrophilic groups to the fiber surface; and differential shrinkage technology, where the filaments in a bundle have different boiling water shrinkage rates, significantly enhancing the fiber's hand feel, bulkiness, moisture absorption, breathability, and dyeability.
[0003] Chinese invention patent application number 200910234717.1 discloses a method for preparing heterogeneous shrinkage polyester filament. This composite fiber is composed of high-shrinkage fully drawn polyester yarn and fine denier low-elasticity polyester yarn. As a type of differentiated polyester fiber, heterogeneous shrinkage polyester filament has the following main characteristics: ① Good bulkiness, softness, and resilience. The appearance of heterogeneous shrinkage polyester filament is similar to ordinary filament. After heat treatment, the high-shrinkage monofilament forms a clearly defined core, becoming the skeleton of the yarn, while the low-shrinkage monofilament forms small loops around the core, resembling textured yarn. The resulting fabric is fluffy and dense, with a full hand feel, and significantly improved texture and luster. ② Improved warmth retention, breathability, and water absorption. The small loops formed by the low-shrinkage monofilament float on the fabric surface, exhibiting a significant capillary effect, thus improving the fabric's breathability, warmth retention, and water absorption. ③ Different shrinkage fibers do not need to undergo further texturing. Compared with textured yarn, their cost can be reduced by 15% to 20%. At the same time, due to their high bulkiness, the weight per square meter of the fabric can be reduced by 5% to 10%.
[0004] Differential shrinkage fibers are mainly used to weave wool-like fabrics. During the dyeing and finishing process, due to differences in shrinkage, the fabric develops a multi-layered, fluffy structure with a finer denier surface fiber density, resulting in a smooth and dry feel against the skin. The high-shrinkage coarser filaments become the core filaments, improving the fabric's elasticity and drape, giving it a fuller hand feel and making it lighter. Differential shrinkage polyester filaments can also be used as architectural decorative fabrics, such as curtains, tapestries, carpets, and home upholstery materials. Therefore, it is necessary to impart flame-retardant properties to differential shrinkage polyester filaments. Generally, due to the difficulty of processing, differential shrinkage polyester filaments are not subject to flame-retardant modification or flame-retardant finishing on textile fabrics. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a differential shrinkage flame retardant and anti-dripping fiber with excellent wool-like and flame retardant effects and its preparation method.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: a method for preparing heteroshrunk flame-retardant and anti-dripping fiber, which involves esterification reaction of terephthalic acid and ethylene glycol, followed by addition of compound flame retardant and polycondensation reaction to obtain melt, and the melt is spun through a heteroshrunk porous spinneret.
[0007] The porous spinneret includes at least two types of irregularly shaped spinneret holes; the method for preparing the compound flame retardant is as follows: mixing and grinding methacrylate-based silicone resin micro powder, whitened red phosphorus and tetra-needle zinc oxide whiskers into micron-sized particles.
[0008] Another technical solution adopted in this invention is: the differential shrinkage flame retardant and anti-dripping fiber prepared by the above preparation method.
[0009] The beneficial effects of this invention are as follows: This invention uses a copolymerization method, adding a compound flame retardant during the polycondensation reaction to form a copolymer-modified polyester melt. This melt is then spun using a melt-spinning process to obtain a heterogeneous shrinkage flame-retardant and anti-dripping fiber. This fiber possesses heterogeneous cross-section and heterogeneous shrinkage characteristics, exhibiting excellent wool-like properties. The compound flame retardant contains methacrylate-based silicone resin micropowder, whitened red phosphorus, and tetraquid zinc oxide whiskers. The combination of methacrylate-based silicone resin micropowder and whitened red phosphorus provides excellent flame retardant effects. The tetraquid zinc oxide whiskers, utilizing their spatial structure, can be embedded within the fiber, effectively preventing the fabric from melting and dripping when heated, thus achieving flame retardant and anti-dripping functions. Attached Figure Description
[0010] Figure 1 The figure shown is a graph illustrating the shrinkage rate variation of the differentially shrunk flame-retardant and anti-dripping fibers at different shaping temperatures in Embodiment 10 of the present invention. Detailed Implementation
[0011] To explain in detail the technical content, objectives, and effects of the present invention, the following description is provided in conjunction with the embodiments and accompanying drawings.
[0012] Please refer to Figure 1 A method for preparing heteroshrunk flame-retardant and anti-dripping fiber involves esterification of terephthalic acid and ethylene glycol, followed by addition of a compound flame retardant and polycondensation to obtain a melt, which is then spun through a heteroshrunk porous spinneret.
[0013] The porous spinneret includes at least two types of irregularly shaped spinneret holes; the method for preparing the compound flame retardant is to mix and grind methacrylate-based silicone resin micro powder, whitened red phosphorus and tetra-needle zinc oxide whiskers into micron-sized particles.
[0014] As can be seen from the above description, the beneficial effects of the present invention are as follows: In the preparation process of the present invention, the melt is spun through a non-circular, non-shrinkage porous spinneret to obtain non-circular, non-shrinkage shaped fibers. Due to the difference in shrinkage, the high-shrinkage coarse filaments of these fibers become the core filaments in the subsequent dyeing and finishing process, improving the elasticity and drape of the fabric. The low-shrinkage surface fibers have a finer denier, making the skin feel delicate and dry, and creating a multi-layered, fluffy structure. The non-circular cross-section design creates more gaps within the fabric, making the fabric feel full and lightweight, thereby greatly improving the grade of the synthetic fiber imitation wool fabric.
[0015] This invention incorporates a compound flame retardant during the polycondensation process. All components of the compound flame retardant are soluble in ethanol, forming a copolymerized modified polyester melt. The compound flame retardant can be added via continuous feeding, enabling continuous production. This flame-retardant modification process is simple, efficient, and highly operable. The compound flame retardant is prepared from methacrylate-based silicone resin micropowder, whitened red phosphorus, and tetraquid zinc oxide whiskers. The combination of methacrylate-based silicone resin micropowder and whitened red phosphorus provides excellent flame retardant effects. The tetraquid zinc oxide whiskers, utilizing their spatial structure, can be embedded within the fiber, effectively preventing the fabric from melting and dripping when heated, thus achieving flame retardant and anti-dripping functions. The micron-sized compound flame retardant mixes more uniformly during the polycondensation reaction, which is beneficial for spinning production.
[0016] Organosilicon resins possess a highly cross-linked network structure, exhibiting excellent flame-retardant properties. Introducing epoxy, methacrylate, and amino groups into organosilicon flame retardants yields methacrylate-based silicone resin micropowders, which not only improves the material's processability but also reduces smoke and heat release during combustion, decreases CO production, and enhances the material's flame-retardant performance. During combustion, its flame-retardant effect is achieved by generating a pyrolytic char layer and improving its oxidation resistance. The silicon-oxygen chain promotes char formation at high temperatures, while the silicon-oxygen chains in the char layer contribute to the formation of a continuous, oxidation-resistant silicate protective layer; thus, it significantly improves the material's oxygen index and high-temperature oxidation resistance, and protects the substrate beneath the char layer from damage.
[0017] The tetraneedle-shaped zinc oxide whisker crystal structure belongs to the wurtzite structure. Macroscopically, it is a white, loose powder, and microscopically, it is a tetraneedle-shaped three-dimensional structure. This allows it to isotropically reinforce composite materials and is not easily pulled out of the matrix, resulting in good compatibility with the matrix.
[0018] Furthermore, the mass of the compounded flame retardant is 1 to 3% of the melt mass.
[0019] As described above, flame retardants are physically fixed onto the polyester molecular chains, providing sites for chain breakage. When the fiber is subjected to external force, it is prone to breakage at the flame retardant fixation points. With increasing flame retardant content, the fiber's breaking strength and elongation at break gradually decrease, while the number of fiber breaks increases. Therefore, controlling the amount of flame retardant added to below 3% can maintain good spinning conditions and optimal mechanical properties.
[0020] Furthermore, the mass ratio of methacrylate-based silicone resin micro powder, whitened red phosphorus, and tetraneedle-shaped zinc oxide whiskers is 2–3:1–1.5:1.
[0021] Preferably, the mass ratio of methacrylate-based silicone resin micro powder, whitened red phosphorus, and tetraneedle-shaped zinc oxide whiskers is 2.5:1.25:1.
[0022] As described above, a majority of the methacrylate-based silicone resin powder and whitened red phosphorus can exert a good flame-retardant effect, while keeping the amount of inorganic additives low can ensure the strength of the fibers. Therefore, the mass ratio of methacrylate-based silicone resin powder, whitened red phosphorus, and tetraneedle-shaped zinc oxide whiskers should be controlled at 2-3:1-1.5:1.
[0023] Furthermore, the esterification reaction of terephthalic acid and ethylene glycol is carried out at a temperature of 240–250 °C.
[0024] Furthermore, antimony glycolate, n-butyl titanate, and trimethyl phosphate were added during the esterification reaction of terephthalic acid and ethylene glycol.
[0025] Furthermore, the temperature of the polycondensation reaction is 273–278°C.
[0026] Furthermore, the melt conveying temperature is 288–292°C.
[0027] Preferably, the melting temperature is 290°C.
[0028] As can be seen from the above description, a higher conveying temperature can reduce the viscosity of the melt at a lower shear rate, which is beneficial for the melt to flow evenly in the pipe and the spinneret flow zone, and improves spinnability. However, if the conveying temperature is too high, it will cause melt degradation, reduce the intrinsic viscosity of polyester, generate gel particles, and increase the phenomena of filament twisting, fuzzing, and breakage. Therefore, the conveying temperature of the melt should be controlled at 288-292℃.
[0029] Furthermore, the spinning temperature is 293–295°C.
[0030] Preferably, the spinning temperature is 295°C.
[0031] As described above, using a higher spinning temperature is beneficial for improving the fluidity of the melt, but it can cause degradation of the melt within the spinning chamber, resulting in phenomena such as yarn breakage and excessive filament drift, and also shortening the pump cycle. Conversely, spinning at too low a temperature can easily lead to increased filament sheathing and the formation of stiff yarn. Therefore, the spinning temperature should be controlled between 293 and 295°C.
[0032] Furthermore, the melt needs to be filtered before spinning. During filtration, the melt passes through 40-60 mesh sand, 60-100 mesh sand and 30-40 mesh sand in sequence; the weight ratio of 40-60 mesh sand, 60-100 mesh sand and 30-40 mesh sand is 40-80:80-120:20.
[0033] Preferably, the weight ratio of 40-60 mesh sand, 60-100 mesh sand and 30-40 mesh sand is 60:80:20.
[0034] As described above, the amount of fine sand used during filtration is crucial. Insufficient fine sand prevents the uniform distribution of the upper melt layer and easily retains impurities, leading to uneven melt flow during spinning and increasing the unevenness rate. By adjusting different sand ratios and increasing the filtration density, impurities in the melt can be significantly reduced, minimizing issues such as fuzz and broken ends. Therefore, the weight ratio of 40-60 mesh sand, 60-100 mesh sand, and 30-40 mesh sand should be controlled at 40-80:80-120:20.
[0035] Furthermore, the blowing conditions after spinning are: air pressure of 20-40℃ and air temperature of 20-22℃.
[0036] Preferably, the blowing conditions after spinning are: air pressure of 40°C and air temperature of 20°C.
[0037] As described above, under the condition of a fixed air outlet area, the higher the air pressure, the faster the air velocity exiting the fine filter screen, and the faster the fiber bundle cools. However, excessive air velocity may create turbulence in the center of the fiber bundle, causing unstable swaying of the inner filaments, uneven cooling of the nascent fibers, resulting in increased evenness and affecting subsequent dyeing performance. Insufficient air velocity will lead to insufficient cooling of the inner filaments, easily causing breakage and filament bundling. Therefore, the blowing conditions after spinning should be controlled as follows: air pressure 20–40 Pa, air temperature 20–22 °C.
[0038] Furthermore, the setting temperature after spinning is 175–180℃.
[0039] Preferably, the setting temperature after spinning is 175°C.
[0040] As described above, during the setting process, the oriented structures with a certain degree of regularity crystallize due to heat, effectively fixing the fiber orientation. Simultaneously, heat causes some oriented structures in the amorphous regions to deorient, eliminating internal stress and improving fiber molecular stability. Excessive setting temperature not only causes yarn vibration, oil evaporation and scaling onto the hot rollers leading to yarn breakage, uneven heating, and poor dyeing uniformity, but also enhances macromolecular chain mobility, increasing crystallinity and decreasing the content of amorphous regions, resulting in lower boiling water shrinkage. Conversely, excessively low setting temperature may lead to uneven dyeing due to uneven crystallization. Therefore, the setting temperature after spinning should be controlled at 175–180℃.
[0041] Furthermore, the draw ratio during spinning is 45 / 89.
[0042] The draw ratio (DR) is the ratio of the linear velocity of the surfaces of the hot roll (GR1) to the hot roll (GR2).
[0043] Furthermore, the oiling rate after spinning is 0.8%–1.0%.
[0044] Preferably, the oiling rate after spinning is 0.9%.
[0045] As described above, if the oiling rate is too low, the friction and tension between the filament and the hot roller will be high, resulting in poor dyeing performance of the filament; if the oil content is too high, it is easy to drip and cause coking when passing through the hot roller, which will worsen the dyeing uniformity. Therefore, the oiling rate after spinning should be controlled at 0.8% to 1.0%.
[0046] Another technical solution adopted in this invention is: the differential shrinkage flame retardant and anti-dripping fiber prepared by the above preparation method.
[0047] As can be seen from the above description, the differential shrinkage flame retardant and anti-drip fiber of the present invention has a good hand feel, a good wool-like effect, and excellent flame retardant and anti-drip functions.
[0048] In the following examples, the amount of compound flame retardant added is the mass of the compound flame retardant / mass of the melt, and the methacrylate-based silicone resin micro powder is from Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.
[0049] Embodiment 1 of the present invention is a method for preparing a differential shrinkage flame-retardant and anti-dripping fiber, the steps of which are as follows:
[0050] S1: A compound flame retardant was prepared by mixing and grinding methacrylate-based silicone resin micro powder, whitened red phosphorus and tetraneedle-shaped zinc oxide whiskers into micron-sized particles.
[0051] S2: Add terephthalic acid and ethylene glycol in a molar ratio of 1:1.3 to the reactor, then add 400 ppm of tetrabutyl titanate and 300 ppm of trimethyl phosphate stabilizer. Displace the esterified product using N2 bubbling and carry out the esterification reaction. Stop the reaction when the amount of water produced by the ester exchange reaches 95% of the theoretical amount. Then add a compound flame retardant and perform a condensation reaction under vacuum to obtain the melt.
[0052] S3: After melt filtration, the fibers are spun through a multi-hole spinneret with different shrinkage, cooled by blowing air, and oiled with an oil nozzle to obtain flame-retardant and anti-dripping fibers with different shrinkage. The structure of the spinneret is the same as that of Chinese invention patent application number 201711422880.1. The process parameters of Example 1 are shown in Table 1. The performance of the flame-retardant and anti-dripping fibers with different shrinkage prepared in Example 1 is tested, and the test results are shown in Table 2.
[0053] Table 1
[0054]
[0055] Table 2
[0056]
[0057] Embodiment 2 of the present invention is as follows:
[0058] The difference between Example 2 and Example 1 is that the process parameters for Example 2 are shown in Table 3.
[0059] Table 3
[0060]
[0061]
[0062] Embodiment 3 of the present invention is as follows:
[0063] The difference between Example 3 and Example 1 is that the process parameters for Example 3 are shown in Table 4.
[0064] Table 4
[0065]
[0066] Example 4 of the present invention is: a differential shrinkage flame retardant and anti-dripping fiber prepared by the preparation method of Example 1.
[0067] Example 5 of the present invention is as follows: Based on Example 1, the effect of different ratios of compound flame retardants on the flame retardant effect of differential shrinkage flame retardant and anti-dripping fibers is tested. The test results are shown in Table 5.
[0068] Table 5
[0069]
[0070] As shown in Table 5, the combustion performance gradually improves as the proportion of methacrylate-based silicone resin micropowder in the compound flame retardant increases. However, the increasing proportion of methacrylate-based silicone resin micropowder leads to a decrease in the content of tetra-needle zinc oxide whiskers, weakening the anti-dripping effect. Therefore, the preferred ratio of the compound flame retardant is 2.5:1.25:1.
[0071] Example 6 of the present invention is as follows: Based on Example 1, the effect of different amounts of compound flame retardant added on the mechanical properties of differential shrinkage flame retardant and anti-dripping fibers was tested. The test results are shown in Table 6.
[0072] Table 6
[0073] 1 1% 3.78 28.37 2.1 2 2% 3.56 26.78 2.6 3 3% 3.25 25.33 3.2 4 4% 2.84 20.88 3.9 5 5% 2.33 19.22 4.3
[0074] As shown in Table 6, with the increase of flame retardant content, the breaking strength and elongation at break gradually decrease, and the number of breakages increases. Therefore, the amount of flame retardant added should be controlled below 3% in order to maintain a good spinning state and better mechanical properties.
[0075] Embodiment 7 of the present invention is as follows: Based on Embodiment 1, the effect of different melt delivery temperatures on the mechanical properties of differential shrinkage flame retardant and anti-dripping fibers was tested, and the test results are shown in Table 7.
[0076] Table 7
[0077] Elongation at break / % 110.2 115.5 119.1 126.4 Elongation at break (CV / %) 3.89 3.57 3.23 2.28 Unevenness rate of strips U / % 1.35 1.18 0.85 1.54 Single fiber strength / (cN / dtex) 2.12 2.21 2.29 2.35 Number of decapitations / (times / position / day) 5.0 3.5 3.0 5.5
[0078] As shown in Table 7, the production situation is most stable when the melt conveying temperature is 290℃.
[0079] Example 8 of the present invention is as follows: Based on Example 1, the effect of different spinning temperatures on the production process of differential shrinkage flame retardant and anti-dripping fibers was detected, and the detection results are shown in Table 8.
[0080] Table 8
[0081] 289 12 1 6 291 10 1 4 293 6 2 2 295 4 2 1 297 9 8 5
[0082] As shown in Table 8, the production performance is better when the spinning temperature is 295℃ than when the spinning temperature is other.
[0083] Example 9 of the present invention is as follows: Based on Example 1, the effect of different mesh size sand loading ratios on the mechanical properties of differential shrinkage flame retardant and anti-dripping fibers is tested. The test results are shown in Table 9.
[0084] Table 9
[0085]
[0086] As shown in Table 9, the high component pressure in the first group leads to a shorter component cycle. In the third and fourth groups, the physical properties of the differential shrinkage flame retardant and anti-dripping fibers decrease significantly. Considering all factors, the sand loading ratio in the second group is selected as the optimal ratio.
[0087] Example 10 of the present invention is as follows: Based on Example 1, the effects of different blowing conditions on the performance of the differential shrinkage flame retardant and anti-dripping fiber are tested, and the test results are shown in Table 10.
[0088] Table 10
[0089]
[0090]
[0091] As shown in Table 10, when the wind pressure is 40 Pa, the wind temperature is 20 °C, and the wind humidity is 90%, the breaking elongation, breaking strength, evenness, and boiling water shrinkage of the differential shrinkage flame retardant and anti-dripping fiber are all at a good level.
[0092] Embodiment 10 of the present invention uses the second hot roller (GR2) temperature as the setting temperature. Based on Embodiment 1, the effect of different setting temperatures on the shrinkage rate of the differential shrinkage flame-retardant and anti-dripping fiber is tested. The test results are shown in […]. Figure 1 .
[0093] Depend on Figure 1 It is known that the higher the temperature of GR2, the lower the boiling water shrinkage rate of the fiber. When the temperature of GR2 is increased to 190℃, the boiling water shrinkage rate can reach 8.8%. This is because the increase in the setting temperature reduces the content of amorphous regions and lowers the boiling water shrinkage rate. However, at this time, the filaments vibrate violently on the GR2 hot roller, which seriously affects the production stability, resulting in more breakage and a decrease in the full roll rate. After multiple experiments, it was determined that the GR2 temperature of 190℃ is the best for producing differential shrinkage flame-retardant and anti-dripping fibers, resulting in the best production conditions and superior quality.
[0094] In Embodiment Eleven of the present invention, the draw ratio (DR) is the ratio of the linear velocity of the surface of the first hot roller (GR1) to that of the second hot roller (GR2). Based on Embodiment One, the effect of different spinning rates on the performance of the differential shrinkage flame-retardant and anti-dripping fiber was tested, and the test results are shown in Table 11.
[0095] Table 11
[0096]
[0097] As shown in Table 11, when GR1 / GR2 is 2550 / 4450, the strength of the differential shrinkage flame retardant and anti-dripping fiber is relatively high, and the production is relatively stable.
[0098] Example 12 of the present invention is as follows: Based on Example 1, the effect of different oiling rates on the dyeing properties of differential shrinkage flame retardant and anti-dripping fibers was tested, and the test results are shown in Table 12.
[0099] Table 12
[0100] 0.7 95.5 Poor 0.8 96.6 generally 0.9 97.9 uniform 1.0 98.0 generally 1.1 97.9 Poor
[0101] As shown in Table 12, when the oil content is 0.9%, the AA index and dyeing performance of the differential shrinkage flame retardant and anti-dripping fiber are both good.
[0102] In summary, the differential shrinkage flame-retardant and anti-dripping fiber and its preparation method provided by this invention have the following advantages:
[0103] (1) By spinning through a non-circular, non-circular, porous spinneret, non-circular, non-circular fibers are obtained, which improves the elasticity and drape of the fabric and produces a multi-layered fluffy structure. The non-circular cross-section design makes the fabric have more gaps, making the fabric feel full and lightweight, thus greatly improving the grade of the chemical fiber imitation wool fabric.
[0104] (2) During the polycondensation process, a compound flame retardant is added. The compound flame retardant, in which methacrylate-based silicone resin micro powder and white red phosphorus are compounded, can achieve excellent flame retardant effect. The four needle-like zinc oxide whiskers can effectively prevent the fabric from melting and dripping when heated, thus achieving flame retardant and anti-dripping functions.
[0105] (3) The amount of flame retardant added is controlled below 3% to maintain a good spinning state and better mechanical properties.
[0106] (4) Optimize process parameters such as the conveying temperature of the melt to enable the differential shrinkage flame retardant and anti-dripping fiber to obtain excellent shrinkage rate and mechanical properties.
[0107] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent modifications made based on the content of the present invention's specification and drawings, or direct or indirect applications in related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing a differential shrinkage flame-retardant and anti-dripping fiber, characterized in that, The melt is obtained by esterification reaction of terephthalic acid and ethylene glycol, followed by addition of compound flame retardant and polycondensation reaction. The melt is then spun through a multi-hole spinneret with different shrinkage. Before spinning, the melt needs to be filtered. During filtration, the melt passes through 40-60 mesh sand, 60-100 mesh sand and 30-40 mesh sand in sequence. The porous spinneret includes at least two types of irregularly shaped spinnerets; the preparation method of the compound flame retardant is as follows: methacrylate-based silicone resin micro powder, whitened red phosphorus and tetraneedle-shaped zinc oxide whiskers are mixed and ground into micron-sized particles; the mass ratio of the methacrylate-based silicone resin micro powder, whitened red phosphorus and tetraneedle-shaped zinc oxide whiskers is 2.5:1.25:
1.
2. The method for preparing heterogeneous shrinkage flame-retardant and anti-dripping fibers according to claim 1, characterized in that, The mass of the compounded flame retardant is 1 to 3% of the melt mass.
3. The method for preparing heterogeneous shrinkage flame-retardant and anti-dripping fibers according to claim 1, characterized in that, The esterification reaction of terephthalic acid and ethylene glycol is carried out at a temperature of 240~250℃.
4. The method for preparing heterogeneous shrinkage flame-retardant and anti-dripping fibers according to claim 1, characterized in that, During the esterification reaction of terephthalic acid and ethylene glycol, antimony glycolate, n-butyl titanate, and trimethyl phosphate were also added.
5. The method for preparing heterogeneous shrinkage flame-retardant and anti-dripping fibers according to claim 1, characterized in that, The polycondensation reaction is carried out at a temperature of 273~278℃.
6. The method for preparing heterogeneous shrinkage flame-retardant and anti-dripping fibers according to claim 1, characterized in that, The conveying temperature of the melt is 288~292℃.
7. The method for preparing heterogeneous shrinkage flame-retardant and anti-dripping fibers according to claim 1, characterized in that, The spinning temperature is 293~295℃.
8. A type of flame-retardant and anti-drip fiber prepared by the method of any one of claims 1-7.
Citation Information
Patent Citations
Composite fiber
CN101724948A
Method for producing flame-retardant melt-drip resistant polyester short fibers
CN102400244A
Preparation method of flame-retardant droplet-resistant terylene
CN102978735A
Production method for producing different-shrinkage fully drawn yarn in one step and spinneret plate special for production method
CN107964689A